Benefits of water intake on kidney function in older adults: protocol for a randomized controlled trial - Mariana Rangel Ribeiro Falcetta; Guilherme Botter Maio Rocha; Leticia Rossetto Daudt; Alice Kieling Bublitz; Maurício Picolo Menegolla; Roberta de Pádua Borges; Andrea Carla Bauer (Brazilian Society of Geriatrics and Gerontology, 2022)
Objective: The goal of this study is to evaluate the benefits of an increase in water intake guided by a mathematical formula (per kg of body weight) on kidney function in older adults. Methods: Older adults (≥ 65 years old) cared for at the Internal Medicine Unit of a tertiary hospital will be randomized to receive or not guidance on water intake (30 mL/kg per day) after initial assessment of kidney function. After 14 days, participants will be reevaluated through clinical and laboratory examinations. Patients with uncompensated disease will be excluded. The main outcomes will be glomerular filtration rate and laboratory measures such as serum and urinary osmolality, sodium, urea, 24-h urine volume and serum creatinine, uric acid, and copeptin. The Mini Nutritional Assessment (MNA) questionnaire will be applied to participants at each visit. Categorical variables will be described as numbers of cases (%) and compared using the χ2 test whereas continuous variables will be analyzed with Student's t-test in relation to baseline measures. The Generalized Estimating Equations (GEE) method will be performed to assess differences over time and between groups. This study was approved by the Institution's Research Ethics Committee (grant number 16-0153) and is in accordance with the Declaration of Helsinki. Expected Results: By increasing water intake (ml/Kg) we expect to provide an improvement in kidney function in older population assessed by serum creatinine and cystatin-c applied to eGFR formulas. Relevance: Many conditions, both organic and behavioral, can contribute to chronic dehydration states in older adults. To mention, decreased ability to concentrate urine, reduced kidney mass, blood flow, and glomerular filtration rate (GFR) along with changes in sensitivity to hormones such as renin, vasopressin and natriuretic peptide can generate water imbalance, leading to dehydration. For being simple and inexpensive, this strategy may be broadly used and bring several health benefits to older adults.